Color Flow Doppler Sonography for the Etiologic Diagnosis of Thyrotoxicosis - Rosario, P. W.; Santos, J. B. N.; Nunes, N. S.; da Silva, A. L.; Calsolari, M. R. (Hormone and Metabolic Research, 2014)
The objective of this prospective study was to compare the results of color flow Doppler sonography (CFDS) and radioiodine scintigraphy in patients with thyrotoxicosis. A total of 176 patients, 102 with clinical thyrotoxicosis and 74 with subclinical dysfunction, were included. Pregnant and breast-feeding women, patients using amiodarone or recently exposed to iodinated contrast, and patients treated with antithyroid drugs were excluded. Total T3, free T4, TSH, and anti-TSH receptor antibodies were measured before scintigraphy and CFDS. Excluding one patient whose etiology of thyrotoxicosis remained undefined, CFDS showed 100% specificity. In fact, in all 10 cases in which scintigraphy and CFDS provided discordant results, the diagnosis suggested by the latter was correct. In patients with clinical thyrotoxicosis, the sensitivity of CFDS was 96% for diffuse toxic goiter, 95% for the absence of hyperfunction, and 100% for toxic nodular disease. In patients with subclinical dysfunction, the sensitivity of CFDS was 72.7% for diffuse toxic goiter, 90% for toxic adenoma, and 86.6% for toxic multinodular disease. CFDS was inconclusive in patients with parenchymal blood flow with patchy uneven distribution or with macronodules in which nodule vascularity compared to the remaining parenchyma did not permit to establish the diagnosis with certainty. CFDS can be used instead of scintigraphy not only in situations in which the latter is contraindicated or of limited value to define the etiology of thyrotoxicosis.
Keywords: color flow Doppler sonography; thyrotoxicosis; etiology